An environmentally viable helmet design using low impact material - Tahk, Yelin; Woo Tahk, Young (Open Science Journal, 2022)
In utilizing Young’s Modulus to determine the elasticity of a material as well as the protecting structure of the human brain, we experimented with various materials to find the most inelastic material that would allow for maximum protection of the brain. Due to the low Young’s Modulus Value presented in Agarose Gel and Silica Aerogel, these would be viable options for a thin, viscous layer of protection inside the helmet. Using an impact car to mimic a head-on collision, we tested agarose gel, silica aerogel, polystyrene, and wood by measuring acceleration and the time duration with the Arduino Science Journal. The objective was to find which material would be the most viable options to create an environmentally safe alternative to polystyrene while maintaining the integrity of the helmet during a collision. Both Silica Aerogel and Agarose Gel had similarity to polystyrene while being a much more environmentally viable option due to their ability to decompose quickly. Agarose Gel is less favorable because it dries up quickly, requires heat to activate, and is prone to breaking. Silica Aerogel is the best option to make the football helmet protectant because it is extremely light, a thermal insulator, and is less prone to breakage.